The role of apology beliefs for apology tendencies across cultures with varying honor norms - Alexander Kirchner-Häusler; Ayse K. Uskul; Michael J.A. Wohl; Vivian L. Vignoles; Susan E. Cross; Rosa Rodriguez-Bailón; Meral Gezici-Yalçın; Charles Harb; Shenel Husnu; Konstantinos Kafetsios; Evangelia Kateri; Juan Matamoros-Lima; et al. (Current Research in Ecological and Social Psychology, 2025)
Apologies serve as crucial tools for relationship repair, promoting reconciliation, and demonstrating accountability. However, beliefs about the morality, effectiveness, and responsibility-signaling nature of apologies may vary across cultures, particularly in contexts shaped by honor norms where apologies fit central cultural concerns for morality and strength in ambiguous ways. This study investigates the relation between apology beliefs and cultural honor norms across 14 Mediterranean, East Asian, and Anglo-Western samples (N = 5296). We assessed personal and normative beliefs about apologies and their alignment with apology tendencies (willingness to apologize and past offered apologies) as well as intersubjectively rated honor norms. Results revealed that stronger beliefs in the morality and effectiveness of apologies, as well as perceptions of apologies as admissions of responsibility, consistently predicted greater willingness to apologize across regions and past apologies offered. Against our expectations, honor norms moderated only a few of these relations, with significant interactions suggesting weaker links between apology beliefs and apology tendencies at stronger honor norms. Complementary analyses comparing regional categorizations (Anglo-West, East Asia, and MENA) further supported a picture of relative cultural similarities but also highlighted a wider array of relevant apology beliefs in the MENA region as well as a greater focus on personal morality beliefs in Anglo Western societies and personal effectiveness beliefs in East Asian societies. Our findings underscore the universal significance of apology beliefs in fostering reconciliation while also revealing some cultural variability in how personal beliefs and cultural norms may interact in shaping apology-related behaviors across diverse societies.